The role of directors' and officers' insurance in corporate governance: evidence from the high-tech industry in Taiwan. (4th May 2007) - Lu, Jung-Ho; Horng, Der-Juinn
By examining the association between board composition, managerial ownership, external shareholder control and the purchase of Directors' and Officers' (D&O) insurance, this paper examines the role of D&O insurance in corporate governance of 292 publicly listed High-Tech Companies (HTCs) in Taiwan. Holderness suggests that D&O insurance has an important governance role in publicly owned companies. O'Sullivan empirically tests Holderness's monitoring hypothesis, the results generally support the monitoring hypothesis. Although our results partly support the monitoring hypothesis, this study cannot only can be considered an important first step in attempting to understand the governance role of D&O insurance but also provide some further insights on the demands for D&O insurance in Taiwan.